2014
DOI: 10.1159/000357438
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Impaired the Functional Activity of Endothelial Colony-Forming Cells

Abstract: Background: Recent studies have shown that endothelial progenitor cells (EPCs) contribute to lung repair after lipopolysaccharide (LPS)-induced lung injury and infusion of LPS decreased early EPCs in human peripheral blood. However, the effects of LPS on endothelial colony-forming cells (ECFCs) remain to be determined. Objective: To investigate possible effects of LPS on the functional activity of ECFCs. Methods: ECFCs were isolated from human umbilical cord blood and characterized. ECFCs at passages 3-5 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…The authors previously demonstrated that LPS impaired the viability, migration, adhesion and in vitro vasculogenesis capacity of late EPCs (13). On this basis, the present study revealed that inhibition of TLR4 signaling can reverse this impairment of functional activity in late EPCs, which suggested that TLR4 signaling pathways may be involved in the LPS-induced dysfunction of late EPCs.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The authors previously demonstrated that LPS impaired the viability, migration, adhesion and in vitro vasculogenesis capacity of late EPCs (13). On this basis, the present study revealed that inhibition of TLR4 signaling can reverse this impairment of functional activity in late EPCs, which suggested that TLR4 signaling pathways may be involved in the LPS-induced dysfunction of late EPCs.…”
Section: Discussionsupporting
confidence: 75%
“…The present study was approved by the ethics committee of Shantou University Medical College (Guangdong, China). Late EPCs were isolated and cultured according to previously MIN YU 1,2* , CANTIAN WANG 1* , GUONING ZENG 1 , LIHONG ZHOU 1 , TINGTING CHEN 1 , XUERUI TAN 1 and YANPING WANG 1 described techniques (3,13,(15)(16)(17). Mononuclear cells (MNCs) were isolated from previously obtained umbilical cord blood from the First Affiliated Hospital of Shantou University Medical College (13) by Ficoll density gradient centrifugation (TDL-5-A, Shanghai Anting Scientific Instrument Factory, Shanghai, China) at 1,000 x g for 20 min at room temperature and cultured on 6-well plates with endothelial cell growth medium (EGM)-2 (Lonza Group, Ltd., Basel, Switzerland Membranes were blocked for 1 h at room temperature with 5% non-fat milk in TBS containing 0.05% Tween-20 (TBST) and incubated with the polyclonal rabbit anti-TLR4 antibody (1:500) at 4˚C overnight, followed by 1 h incubation at room temperature with a horseradish peroxidase-conjugated secondary goat polyclonal anti-rabbit antibody (cat.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Anyway, in our study, adhesion capacity of “early” EPCs was strengthened by treatment with LG. Moving from “early” EPCs to endothelial colony-forming cells (ECFCs), also called “late” EPCs, it is worthy to mention that incubation with LPS inhibited the viable, migratory, adhesive, and in vitro vasculogenesis capacity of ECFCs isolated from human umbilical cord blood [48]. …”
Section: Discussionmentioning
confidence: 99%